Brain-Derived Neurotrophic Factor and Oxytocin Signaling in Association With Clinical Symptoms in Adolescent Inpatients With Anorexia Nervosa—A Longitudinal Study - Tyszkiewicz-Nwafor, Marta; Rybakowski, Filip; Dmitrzak-Weglarz, Monika; Skibinska, Maria; Paszynska, Elżbieta; Dutkiewicz, Agata; Słopien, Agnieszka (Frontiers in Psychiatry, 2020)
Brain-derived neurotrophic factor (BDNF), as well as oxytocin (OXY), are centrally secreted neuropeptides regulating a range of physiological processes, including food intake and metabolism. Numerous reports suggest their role in affective and cognitive symptoms of various psychiatric disorders. The study aimed to measure the serum level of BDNF and its receptor - tropomyosin-related kinase B (TrkB) and OXY in malnourished anorexia nervosa patients and following partial weight-recovery. The correlations between levels of these proteins with the primary symptoms of the anorexia nervosa (AN) were also analyzed. Eighty-four adolescent AN patients were recruited into the study, but only forty-two AN patients completed it. The control group comprises of thirty age- and hight-matched girls (CG). Serum BDNF, TrkB, and OXY levels were measured in AN group in two time-points - at the beginning of the hospitalization in malnourished patients (AN-T1) and again after partial weight normalization, on the day of discharge (AN-T2). The severity of eating disorders, as well as depressive and obsessive-compulsive symptoms, were assessed at the same two-time points. Body Mass Index (BMI) differed significantly between the AN-T1, AN-T2, and CG. BDNF levels for the AN-T1 increased significantly in comparison to the AN-T2, but at two-time points were significantly lower than in the CG. The OXY level did not change with weight gain and in both groups, AN-T1 and AN-T2 were statistically significantly higher than in the CG. Statistically significant negative correlations between BDNF and the severity of eating disorders symptoms were found. Depressive and obsessive-compulsive symptoms did not show significant correlations with levels of studied proteins for either malnourished or partially weight recovered AN patients. BDNF serum levels are decreased in the malnourished AN patients and tended to normalize with partial weight recovery. OXY serum levels were found to be increased in the malnourished AN patients and did not normalize with partial weight recovery, confirming previous reports about its role in the etiopathogenesis of AN. BDNF can be related to aberrant eating behaviours occurring in AN. Our results do not support the role of serum levels of BDNF, TrkB or OXY in the modulation of depressive obsessive-compulsive symptoms.